Secular Variation of Early Cretaceous Granitoids in Kyushu, SW Japan: The Role of Mélange Rocks as a Possible Magma Source - Suga, Kenshi; Yeh, Meng-Wan (Frontiers in Earth Science, 2020)
The Early Cretaceous volcanic-arc granitic rocks from Kyushu, SW Japan are contemporaneous with the granitic rocks of the Yanshan Orogeny (SE China) along the eastern Eurasian continental margin. The secular geochemical variations of the whole-rock major elemental and Sr–Nd isotope data of the Early Cretaceous granitic rocks from Kyushu, SW Japan, as well as the zircon and apatite saturation temperatures, shows distinct changes during the Albian (∼115 to ∼100 Ma) as: (1) the mASI value of the rocks (i.e., Shiraishino granodiorites) decreases below 1, (2) the Sr–Nd isotopic data are relatively constant [87Sr/86Sri = 0.70471 to 0.70573; εNd(t) = + 0.2 to + 1.9] within different rock types including granites, granodiorites, tonalites, and adakitic rocks (i.e., the Shiraishino granodiorites), following the increase of 87Sr/86Sri and decrease of εNd(t) from Berriasian, and (3) higher maximum temperatures at ∼105 Ma. The secular changes indicate that important geodynamic changes occurred in the arc system of SW Japan as it changed from subduction-accretion during the Jurassic to continental arc during the Early Cretaceous. Thermodynamic partial melting modeling demonstrates that the Albian granitic rocks can be derived from mélange rocks, such as chlorite-actinolite schists, at moderate depth and variable redox conditions. It is concluded that the genesis of the Early Cretaceous granitic rocks from Kyushu, SW Japan, may be related to upwelling of the asthenosphere and hot corner flow into the mantle wedge caused by slab rollback, which followed a shallowing of the subduction angle and subsequent flat-slab subduction during the Late Jurassic. The resultant heat induced the partial melting of the mélange rocks that formed on and were transported from the subducted plate interface.